Loneliness, social isolation, their synergistic interaction, and mortality - Beller, Johannes; Wagner, Adina (Health psychology, 2018)
Although loneliness and social isolation are distinct constructs, only few studies have examined the putative synergistic effects of loneliness and social isolation on health. The current study strives to fill this gap. We ask, "Do loneliness, social isolation, and their interaction predict mortality?" We used a large nationally representative sample of middle-aged and older adults in Germany (N = 4,838) with a follow-up period of up to 20 years. We found that the effects of loneliness and social isolation synergistically interact with each other: The higher the social isolation, the larger the effect of loneliness on mortality, and the higher the loneliness, the larger the effect of social isolation. Both constructs are important in predicting health. Researchers and practitioners should consider loneliness, social isolation, and their interaction whenever possible. (PsycINFO Database Record